Spatially inhomogeneous competition between superconductivity and the charge density wave in YBa2Cu3O6.67 - J. Choi (Nature Portfolio, 2020)
Magnetic field induced competing phases in high-temperature superconductors provide a testbed for various theoretical scenarios. Here, Choi et al. report evidence of inhomogeneous superconducting state due to the different competition strength between two charge density wave orders in YBa2Cu3O6.67.